Estimation of the Secondary Attack Rate for Delta Hepatitis Coinfection among Injection Drug Users - Christiane Poulin; Theresa Gyorkos; Lawrence Joseph (Canadian Journal of Infectious Diseases)
The secondary attack rate for delta hepatitis coinfection was estimated among a cluster of injection drug users (IDUs). The infections occurred during an epidemic of hepatitis B in a rural area of Nova Scotia in 1988 and 1989. Six IDUs formed a cluster of delta hepatitis coinfections, representing the first reported outbreak of delta hepatitis in Canada. Contact-tracing was used to identify a cluster of 41 IDUs potentially exposed to delta hepatitis. The index case of delta hepatitis coinfection was presumed to have led to five secondary cases. The secondary attack rate was estimated to be 13.2% (95% confidence interval 0.044 to 0.281). The estimated secondary attack rate may be a useful predictor of disease due to delta hepatitis coinfection in similar IDU populations.